1999
DOI: 10.1039/a908203d
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion coefficients of zirconocene–borate ion pairs studied by pulsed field-gradient NMR—evidence for ion quadruples in benzene solutions

Abstract: Diffusion coefficients for ion pairs containing zirconocene cations and fluorinated tetraphenyl-or methyltriphenylborate anions in benzene solutions are substantially smaller than those expected for monomeric species and indicate that ion quadruples are present in these solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 15 publications
3
68
0
1
Order By: Relevance
“…Beck et al have claimed on the basis of diffusion NMR experiments that the formation of ion quadruples (B) from simple ion pairs (A), as shown in Scheme 6, is probably more important than previously thought in zirconocene-based catalytic systems. [105] This was concluded by measuring the diffusion coefficient of the zirconocenes 73-77 (Scheme 6), and by comparing the findings with the diffusion coefficient obtained for a series of ion pairs such as 73 a/b and 77 a/b with the diffusion coefficient of 73 c, for which the binuclear structure was previously established by X-ray crystallogra- …”
Section: Diffusion Nmr Spectroscopymentioning
confidence: 97%
“…Beck et al have claimed on the basis of diffusion NMR experiments that the formation of ion quadruples (B) from simple ion pairs (A), as shown in Scheme 6, is probably more important than previously thought in zirconocene-based catalytic systems. [105] This was concluded by measuring the diffusion coefficient of the zirconocenes 73-77 (Scheme 6), and by comparing the findings with the diffusion coefficient obtained for a series of ion pairs such as 73 a/b and 77 a/b with the diffusion coefficient of 73 c, for which the binuclear structure was previously established by X-ray crystallogra- …”
Section: Diffusion Nmr Spectroscopymentioning
confidence: 97%
“…Recently, diffusion data on dendrimers [15 ± 20] and peptides [21 ± 24] as well as on molecules in various environments, e.g., in porous silica [25], and zeolites [26], have been obtained. However, there are very few applications of PGSE methods in coordination and/or organometallic chemistry [27 ± 35].In an interesting and recent application, Beck et al [27] have studied the polymerization catalyst precursors 1 ± 5. Their results prompted the authors to suggest that these zirconium complexes can exist as ion-quadruples in the presence of a boronbased cocatalyst.…”
mentioning
confidence: 99%
“…In an interesting and recent application, Beck et al [27] have studied the polymerization catalyst precursors 1 ± 5. Their results prompted the authors to suggest that these zirconium complexes can exist as ion-quadruples in the presence of a boronbased cocatalyst.…”
mentioning
confidence: 99%
“…The bimolecular mechanism might involve the aggregation of two 1 b ion pairs in a transition state which should resemble the ion quadruples described by Brintzinger et al [6,36] However, this would not explain the observed variation of the bandwidth of the Me-B signal, which can arise only from the presence of an exchange partner, that is, a different ion pair containing a [MeB(C 6 F 5 ) 3 ] À anion. Such partner has been detected by 2D EXSY experiments at 300 K ( Figure S9, Supporting Information), that showed an exchange crosspeak between Me-B of 1 b and a very weak and broad resonance, undetectable in the normal 1D spectrum; the d value shifted from 0.84 to % 1.10 ppm on decreasing the concentration.…”
mentioning
confidence: 84%